Comprehensive Survey of Big Data Mining Approaches in Cloud Systems - Zainab Salih Ageed; Subhi R. M. Zeebaree; Mohammed Mohammed Sadeeq; Shakir Fattah Kak; Hazha Saeed Yahia; Mayyadah R. Mahmood; Ibrahim Mahmood Ibrahim (Qubahan Academic Journal)
Cloud computing, data mining, and big online data are discussed in this paper as hybridization possibilities. The method of analyzing and visualizing vast volumes of data is known as the visualization of data mining. The effect of computing conventions and algorithms on detailed storage and data communication requirements has been studied. When researching these approaches to data storage in big data, the data analytical viewpoint is often explored. These terminology and aspects have been used to address methodological development as well as problem statements. This will assist in the investigation of computational capacity as well as new knowledge in this area. The patterns of using big data were compared in about fifteen articles. In this paper, we research Big Data Mining Approaches in Cloud Systems and address cloud-compatible problems and computing techniques to promote Big Data Mining in Cloud Systems.